Microbial Assessment of Kappaphycus alvarezii and Caulerpa racemosa from Local Market Harvested in Barobo, Surigao Del Sur, Philippines - Mae, Soijairah; A. Avila, Maria Cristina; M. Griño, Jonna Grace; Rexie P. Magdugo (Jurusan Biologi Universitas Negeri Makassar, 2025)
The practice of eating fresh seaweed is needed to assess the microbiological aspects of the seaweed, as it may contain pathogens hazardous to human health. This study aimed to assess the bacterial load of the fresh edible seaweeds Caulerpa racemosa and Kappaphycus alvarezii that are collected from the wild and then sold to public markets. All seaweed samples collected from wild and public markets are examined for aerobic bacteria (Aerobic Plate Count), coliforms (Coliform Count), Salmonella, and E. coli. The results revealed that the coliform, Salmonella, and E. coli were absent in all samples. The aerobic bacteria from the Caulerpa racemosa and Kappaphycus alvarezii collected from the public market were within the limits of the food quality standards set by JECFA, FDA-Philippines, and Food standards of Australia and New Zealand. As for Kappaphycus alvarezii collected from the wild revealed a higher Aerobic Plate count and has exceeded the limits on the food quality standard set by the agencies stated. This study concludes that Caulerpa racemosa and Kappaphycus alvarezii from the public market conform to the requirements of the food quality standards and that sanitary handling of edible seaweeds sold to public markets was properly practiced.